Design of hierarchically tailored hybrids based on nickle nanocrystal-decorated manganese dioxides for enhanced fire safety of epoxy resin - Yuan, Yao (2023)
A novel and hierarchical hybrid composite (MnO2@CHS@SA@Ni) was synthesized utilizing manganese dioxide (MnO2) nanosheets as the core structure, self-assembly chitosan (CHS), sodium alginate (SA) and nickel species (Ni) as surface layers, and it was further incorporated into an epoxy matrix for achieving fire hazard suppression via surface self-assembly technology. Herein, the resultant hybrid epoxy composite possessed an exceptional nano-barrier and synergistic charring effect to aid the formation of a compact layered structure that enhanced its fire-resistive effectiveness. As a result, the addition of only 2 wt% MnO2@CHS@SA@Ni hybrids led to a dramatic reduction in the peak heat release rate and total heat release values (by ca. 33% and 27.8%) of the epoxy matrix. Notably, the peak smoke production rate and total smoke production values of EP/MnO2@CHS@SA@Ni 2% were decreased by ca. 16.9 and 38.4% compared to the corresponding data of pristine EP. This was accompanied by the suppression of toxic CO, NO release and the diffusion of thermal pyrolysis gases during combustion through TG-IR results. Overall, a significant fire-testing outcome of the proposed hierarchical structure was proven to be effective for epoxy composites in terms of flammability, smoke and toxicity reductions, optimizing their prospects in other polymeric materials in the respective fields.